2014
DOI: 10.1515/roe-2014-0204
|View full text |Cite
|
Sign up to set email alerts
|

The Taylor Rule and Financial Stability – A Literature Review with Application for the Eurozone

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 62 publications
0
22
0
2
Order By: Relevance
“…Since the Australian mortgage market relies heavily on variable rate mortgages, variable mortgage loans are subject to high interest rate risk. Financial stability risk is infused as a result of changes to monetary policy (Käfer, 2014). Furthermore, as house prices are directly affected by interest rate shocks, the risk of housing bubbles occurring increases.…”
Section: Data Samplementioning
confidence: 99%
“…Since the Australian mortgage market relies heavily on variable rate mortgages, variable mortgage loans are subject to high interest rate risk. Financial stability risk is infused as a result of changes to monetary policy (Käfer, 2014). Furthermore, as house prices are directly affected by interest rate shocks, the risk of housing bubbles occurring increases.…”
Section: Data Samplementioning
confidence: 99%
“…These considerations necessarily raise the question whether the analysis framework usually used by central banks is the right instrument to derive scientific guidance for policy makers. Existing research in this field is yet still dominated by studies using DSGE models as underlying framework for the analysis [Käfer (2014); Chatelain and Ralf (2014); Plosser (2014)]. In this context, Mishkin (2011) states that the underlying linear quadratic framework of pre-crisis theory of optimal monetary policy has a significant shortcoming, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Beckman and Wilde (2013) found that real exchange rates adjust and the mean reverts much faster in case of large deviations from equilibrium exchange rates. Kafer (2014) indicated that the Taylor rule should be augmented with exchange rates, asset prices, credit, and spreads. Coibion and Goldstein (2012) found that the Federal Reserve responds disproportionately in low unemployment states.…”
Section: Theoretical Aspectsmentioning
confidence: 99%